Mestrado 100% EAD: contribuições para um grupo de servidores da Universidade Federal do Amazonas - Morais, Márcia Andréia Albuquerque de (2022)
In order to raise the contributions of a 100% online Master's degree to a group of servers of the Federal University of Amazonas, this work was carried out through an exploratory research, based on a bibliographic review and a case study. It was based on Oliveira’s studies (2016), on the contributions of IT to teaching; the approaches of Souza, Vilaça and Teixeira (2021), about the use of active methodologies in Distance Learning; Cabral's (2020) analyses on the evolution of graduate studies in Brazil. From this perspective, the issue of the explosion of technologies in the educational field and the importance of professional qualification is addressed. In Higher Education, the proof of the great technological advance is Distance Learning (Distance Learning) that provides academic training with the use of technological resources. Schedule flexibility, cost reduction and other benefits are cited as advantages by students of the EaD modality. With the modality, institutions seek tools that help learning and strategies that place the student as the protagonist in the learning teaching process: active methodologies. The offer of EaD postgraduate courses has enabled the opportunity of qualified training for many professionals. Although the EaD stricto sensu Graduate Program in Brazil is not yet a reality, the opportunity to conduct a 100% online Master's course at a foreign university met the expectations of students who pointed out as positive points the flexibility of schedules made possible by the course, the format of the offer and the ways of addressing the contents.